Kurikulum Pendidikan Anak Usia Dini Tinjauan Psikologi dan Al-Quran - Titin Sumarni (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2021)
Abstract This article discusses how to instil religious values ??in early childhood, three aspects that must be considered are age, physical, and psychological aspects of the child. Early childhood education curriculum in psychology review includes developmental psychology, learning psychology and social psychology, and learning. The psychological review curriculum and the Koran are the concepts of faith and charity and morals that have implications for children's psychological development who have good character with the characters of the values ??of faith, faith, tawhid, gratitude, respect for parents, responsibility, tolerance, patience. , tawaduk, amar ma'ruf, and nahi mungkar. Keywords: curriculum, early childhood education, psychology and Al-Qur'an.